On-off infrared absorption of the S=O vibrational probe of dimethyl sulfoxide - Chakrabarty, Suranjana; Deshmukh, Samadhan H.; Barman, Anjan; Bagchi, Sayan; Ghosh, Anup (Journal of Physical Chemistry B, 2022)
Dimethyl sulfoxide (DMSO), a polar solvent molecule, is used in a wide range of therapeutic and such as dimerization and hydrogen bonding with water, are crucial to understanding the role of DMSO in applications. Herein, we study DMSO in various solvation environments to decipher the environment-dependent dimerization and hydrogen-bonding propensity. We use a combination of infrared spectroscopy, quantum mechanical calculations, and molecular dynamics simulations to reach our conclusions. Although DMSO can exist in a dynamic equilibrium between monomers and dimers, our results show that the relative intensity of the S=O stretch and the CH3 rocking modes is a spectroscopic indicator of the extent of DMSO dimerization in solution. The dimerization (self-association) is seen to be maximum in neat DMSO. When dissolved in different solvents, the dimerization propensity decreases with increasing solvent polarity. In the presence of a protic solvent, such as water, DMSO forms a hydrogen bond with the solvent molecules, thereby reducing the extent of dimerization. Further, we estimate the hydrogen-bond occupancy of DMSO. Our results show that DMSO predominantly exists as doubly hydrogen-bonded in water.

Perturbation of fermi resonance on hydrogen-bonded > C=O: 2D IR studies of small ester probes - Sakpal, Sushil; Chakrabarty, Suranjana; Reddy, Kambham Devendra; Deshmukh, Samadhan H.; Biswas, Rajib; Bagchi, Sayan; Ghosh, Anup (Journal of Physical Chemistry B, 2024)
We utilized linear and 2D infrared spectroscopy to analyze the carbonyl stretching modes of small esters in different solvents. Particularly noteworthy were the distinct carbonyl spectral line shapes in aqueous solutions, prompting our investigation of the underlying factors responsible for these differences. Through our experimental and theoretical calculations, we identified the presence of the hydrogen-bond-induced Fermi resonance as the primary contributor to the varied line shapes of small esters in aqueous solutions. Furthermore, our findings revealed that the skeletal deformation mode plays a crucial role in the Fermi resonance for all small esters. Specifically, the first overtone band of the skeletal deformation mode intensifies when hydrogen bonds form with the carbonyl group of esters, whereas such coupling is rare in aprotic organic solvents. These spectral insights carry significant implications for the utilization of esters as infrared probes in both biological and chemical systems.